Energy impact evaluation of different low-GWP alternatives to replace R134a in a beverage cooler. Experimental analysis and optimization for the pure refrigerants R152a, R1234yf, R290, R1270, R600a and R744. (15th March 2022) - Sánchez, D.; Andreu-Nácher, A.; Calleja-Anta, D.; Llopis, R.; Cabello, R.
Highlights: Six low-GWP alternatives of R134a have been experimentally analysed and compared. A beverage cooler was used as test bench analysing its energy consumption. Hydrocarbons R290, R1270 and R600a introduce energy savings of 27.5%, 26.3% and 1.2%, respectively. HFC R152a and the R744, allows reducing up to 13.7% and 3.9%, respectively. The HFO R1234yf increases the energy consumption to 4.1% concerning R134a. Abstract: Due to the entry into force in 2014 of the European F-Gas Regulation n° 517/2014 and the subsequent Kigali amendment, the phase-out of the medium and high-GWP refrigerants has speeded up in all refrigeration fields. The effect on the plug-in or stand-alone systems has meant that other environmentally friendly refrigerants must replace the R134a with low or ultra-low GWP maintaining the same operating conditions and reducing the energy consumption. Extended examples of these fluids are the hydrocarbons R600a and R290 and the inorganic fluid R744 (CO2 ). However, there are other alternatives to the HFCs R152a and R1234yf or the hydrocarbon R1270 that have hardly been analysed and can make a positive contribution to this sector. Accordingly, this work aims to evaluate the behaviour of a commercial beverage cooler experimentally when it is optimised with six alternatives to the HFC R134a: R152a, R1234yf, R290, R1270, R600a and R744. Results demonstrated that fluids R290, R1270, R152a, R744 and R600a reduce the energy of R134a in 27.5%, 26.3%, 13.7%, 3.9% and 1.2%, respectively, while the use of R1234yf increases the energy usage to 4.1%.